Eugene O’Neill’s the straw as an unexpressionist play: an expressionist study of the concepts of forlornness, communication, and revivification - Maleki, Nasser; Jeihouni, Mojtaba (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
O’Neill’s fascination with the morbid lacerations of life somehow finds voice in almost all his plays. This could certainly be traced to his discomposed life of dolefulness which decidedly is the mainspring of his great competence in representing the trials and tribulations of men from new directions. His early play, The Straw (1919), despite its dramatic and intellectual appeal, unfortunately, has not been subject of much study by scholars. In this play, the amalgamation of the heroine Eileen with the insecure patterns of life and her appalling quarantine force her into the slough of despond with which she has to fight with all available resources. O’Neill’s remarkable power of character drawing takes us into Eileen's world of anguish so that the voiceless cry may find room for expression in a mechanized age. Expressionism is verily traceable in the play but not in the conventional sense. Consequently, this study is expected to delve into the disoriented personality of Eileen, whose isolation stymies a gratifying communication with the world around her, from expressionist bedrock in order to bring to surface the long lost hope of the disconsolate individual. In addition, the paper will also essay to lay stress on the concept of revival from an expressionist perspective through which man can attain placidity and order in a mind-blowing disorderly world.